Determination of glomerular function in advanced renal failure. Issue 9 (September 1977) - Manz, F; Alatas, H; Kochen, W; Lutz, P; Rebien, W; Schärer, K
Abstract : In 15 children with advanced chronic renal failure, glomerular filtration rate was determined by different methods. Inulin clearance correlated well with the mean of creatinine and urea clearance, and also with 51-chromium edetic acid (EDTA) clearance measured over 24 hours. The absolute values of creatinine clearance and of 51Cr-EDTA clearance measured up to 8 hours were higher than inulin clearance. In advanced renal failure both the 51Cr-EDTA clearance measured over 24 hours, and the mean of creatinine and urea clearance, provide acceptable estimates of true glomerular filtration rate.